Trace mineral supplementation in cattle reduces somatic cell count: Evidence from Farmer FIRST Programme - Singh, Amandeep; Singh, Parminder; Tulla, Gurpreet Kour; Grewal, R. S. (Indian Farming, 2025)
The intervention to prevent mastitis through nutritional interventions was undertaken under the ICAR’s flagship extension programme entitled Farmer FIRST Programme. It was found in earlier surveys that there was prevalence of mastitis in the adopted villages. To address this, trace mineral feeding was chosen as a strategic technological input along with advisories on ration balancing, andprevention of mastitis. The somatic cell count was chosen as an indicator of assessment, which is widely used for assessing the milk quality and diagnosing sub-clinical mastitis. Among the adopted villages in District Barnala, two villages namely Hamidi and Dhaner were selected for the intervention, from which a total of 90 cattle farms, 45 from each village with less than 10 dairy animals were selected for methodological coherence and prescriptive standards of biological research. Commercially available trace mineral supplement (comprising Zn, Cu, Mn and Fe) was distributed to the beneficiary farms and advised to feed the same to cattle at the rate of 20g/animal/day for 30 days. The data for somatic cell counts (SCC) were collected before and after the intervention from 90 farms. The results revealed drop in somatic cell count in milk from average 196.99 x 103 cells/ml of milk to 159.22 x 103 cells/ml which was found significant. However, it may be a small decrease in SCC as far as mastitis was concerned but provided evidence, which aligns with the established pattern of science, proved concerted role of trace mineral supplementation in prevention of mastitis.